Sustainable Intensification of Forage Cactus by Intercropping Increases Productivity, Profitability and Water Use Efficiency - Salvador, Kaique Renan da Silva; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Alves, Cleber Pereira; Morais, José Edson Florentino de; Araújo Júnior, George do Nascimento; Souza, Carlos André Alves de; Silva, Marcelo José da; Santos, João Pedro Alves de Souza; Silva, Gabriel Italo Novaes da; Santos, Agda Raiany Mota dos; Souza, Luciana Sandra Bastos de; Queiroz, Mário Adriano Ávila; et al. (Wiley, 2025)
The objective of this study was to evaluate the changes in growth, productive performance, soil water dynamics, efficiency and economic return in production systems with forage cactus under monoculture and intercropping. The two experiments were conducted during 2017 and 2020 in the semi-arid region of Brazil. The forage cactus experiment involved monoculture and intercropping with pigeon pea, forage sunflower and sorghum (‘2502’) in all systems with mulch in the soil. The second forage cactus experiment involved monoculture and intercropping with millet and sorghum varieties (‘SF15’ and ‘1011’) without mulch in the soil. The cutting time was reduced by 155 accumulated degree-days (51 days) in the cactus-‘1011’ system. The cactus-‘2502’ and cactus-‘SF15’ systems presented the highest yields, with fresh and dry matter values equal to 272 and 52 Mg ha−1 (~13 months) and 1025 and 93 Mg ha−1 (~16 months), respectively. In general, the actual evapotranspiration of the intercropped crops was relatively high in terms of revenue, with the cactus-‘SF15’ crop standing out (US$ 26,100). Although intercropping affects the individual growth of the forage cactus, it promotes greater productivity (cactus-‘2502’ and cactus-‘SF15’), earlier cutting (cactus-‘1011’), water use efficiency (cactus-‘2502’ and cactus-‘SF15’) and economic return for the production system (cactus-‘2502’ and cactus-‘SF15’).
Keywords: intercropping; Opuntia; semi-arid; sustainable intensification; water balance